On the use of OpenEHR in a portable PHR - Santos, Cândido (2013)
Quality medical acts rely on patient medical information. With paper records, the responsibility of gathering the disparate information and making it available to the caregivers, falls exclusively upon the patient. This still is, to great extent, the case with electronic health documents. The consensus is that the advantages of patient involvement in his own health are numerous. With the advent of recent technologies and their deployment in healthcare, new ways of involving the patient and making him an active part of his own health are possible. Electronic Health Records (EHR) and specially Personal Health Records (PHR) are important tools for patient empowerment but data population and management through non-intuitive structured forms is time consuming, takes a great amount of effort, and can be deterring specially for people that are not very computer-oriented. PHRs can be simple and scalable applications that the patient uses to get started and afterwards evolve towards complexity. In any case, compliance with standards must be accomplished. In this paper we present a PHR simple to use, implemented on a USB Flash pen for mobility, and compliant with the openEHR specification. Our model builds on openEHR and adds security and privacy features, allows patient data management and can work as an information repository.